Development of Genetic Evaluation on Dairy Cattle Based on Milk Production - Heni Indrijani (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2009)
This paper is aimed to review the development of genetic evaluation on dairy cattle based on milk production, including recording system, mathematical model of the milk curve, genetic parameters, and genetic model for predicting breeding values. Test day is the best system to record milk yield as it can be used to predict lactation curve and genetic parameters. Ali-Schaeffer curve was the best curve to estimate milk yield (r > 0.99). Fixed and random regression models have been widely used to give more advantages in breeding program. The models are able to analyse the records measured at different stage of lactation, and  to predict a total breeding value from incomplete and part records. For practically used, fixed regression model (MRT) is suggested because it does not have numerical problem and is easier to be used.   Key words: Dairy cattle, breeding value, test day, random regression, fixed regression